2005
DOI: 10.1143/jjap.44.343
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of (001)ZrN Thin Films on (001)Si by Low Temperature Process

Abstract: We have prepared (001)ZrN films epitaxially grown on (001)Si substrates by a low temperature process using an ultrahigh vacuum magnetron sputtering system, and evaluated their epitaxial relationships and film qualities, using X-ray diffraction (XRD) analysis, X-ray pole figure, grazing incidence angle X-ray reflectivity (GIXR), transmission electron microscopy (TEM) and atomic force microscopy (AFM). It is clarified that (001)ZrN films grow epitaxially on (001)Si even at room temperature with the directional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…It was also found that the film resistivities were strongly dependent on the N 2 flow ratio and that the film crystallinities were dependent on P DC and T s . The optimum sputtering conditions obtained were as follows: an N 2 flow ratio of 3% and a P DC of 15 W. Furthermore, it was found that epitaxial growth of high-quality stoichiometric (0 0 1)ZrN films with a resistivity of 17 mO cm comparable to that of bulk ZrN ð13:6 mO cmÞ was achieved on (0 0 1)Si at T s ¼ 500 C under the sputtering conditions described in our recent paper [11]. However, the epitaxial growth of (1 1 1)ZrN films at relatively low temperatures has not yet been reported.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…It was also found that the film resistivities were strongly dependent on the N 2 flow ratio and that the film crystallinities were dependent on P DC and T s . The optimum sputtering conditions obtained were as follows: an N 2 flow ratio of 3% and a P DC of 15 W. Furthermore, it was found that epitaxial growth of high-quality stoichiometric (0 0 1)ZrN films with a resistivity of 17 mO cm comparable to that of bulk ZrN ð13:6 mO cmÞ was achieved on (0 0 1)Si at T s ¼ 500 C under the sputtering conditions described in our recent paper [11]. However, the epitaxial growth of (1 1 1)ZrN films at relatively low temperatures has not yet been reported.…”
Section: Introductionmentioning
confidence: 80%
“…Sample preparation was carried out after evacuation to less than 3 Â 10 À8 Torr using the same UHV DC magnetron sputtering system as in our previous study [11]. As substrate, n-(1 1 1)Si wafers were used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations